KELAYAKAN PENUNTUN PRAKTIKUM STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN DENGAN INFORMASI KETEBALAN DAUN DAN LAJU TRANSPIRASI - Chindy Sulastri Ningsih (FKIP Universitas Tanjungpura, 2022)
This study determined the feasibility of a submaterial practical guidelines for tissue structure and function in plants of class XI SMA with information of leaf thickness and transpiration rate as teaching materials. The research method was descriptive. Validation of practical guidelines consisted of two stages, namely instruments and practical guidelines validation. Instrument validation was carried out by one biology education lecturer at FKIP UNTAN and one biology teacher for class XI SMA Pontianak. Validation of the practical guidline was conduted by 5 validators including 2 biology educaton lecturers at FKIP UNTAN and 3 biology teachers for class XI SMA Pontianak. Validation use questionnaire with for aspect an 15 criteria filled using likert scale and analised by lawshe method. Researh of validation pratical guidelines often CVR value of 0.88. Practical guidelines requires improvement of material, construction, practicality and performance aspects to be use as learning proses.